2017
DOI: 10.1017/s2045796017000701
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity among people with severe mental disorder in a rural Ethiopian setting: a comparative, population-based study

Abstract: Efforts to alleviate food insecurity need to target people with SMD as a vulnerable group. Addressing the disabling effects of SMD would also be expected to reduce food insecurity. Access to mental health care integrated into primary care is being expanded in this district as part of the Programme for Improving Mental health carE (PRIME). The impact of treatment on disability and food insecurity will be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
2
30
1
Order By: Relevance
“…In a facility-based, case-control study in India, people with SMD were reported to be more deprived in terms of food insecurity (15.1% higher) compared to their controls [10]. In our previous study, we found that households of people with SMD in a rural district were more likely to be severely food insecure compared to households without a person living with SMD [11].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a facility-based, case-control study in India, people with SMD were reported to be more deprived in terms of food insecurity (15.1% higher) compared to their controls [10]. In our previous study, we found that households of people with SMD in a rural district were more likely to be severely food insecure compared to households without a person living with SMD [11].…”
Section: Introductionmentioning
confidence: 74%
“…No mental health service was available in the district at the time of the study. The data for this study were collected at the baseline of the PRIME intervention [11]. Sodo district was selected for the PRIME study on the basis of sharing characteristics of most districts in Ethiopia [17].…”
Section: Settingmentioning
confidence: 99%
“…For people with SMI living in low‐ and middle‐income countries (LMICs), the situation can be particularly stark due to insufficient access to disability payments or other forms of social welfare . Indeed, we found previously that one‐third of households with a person with SMI in a rural Ethiopian community were affected by severe food insecurity, an extreme manifestation of poverty . This level of food insecurity was significantly higher than that seen in the general population.…”
Section: Introductionmentioning
confidence: 83%
“…Recruitment procedures have been described in detail previously . In brief, community key informants detected people with possible SMI and referred them to the nearest health centre for assessment and initiation of treatment by the trained PHC worker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation